READING IN AN INTERMEDIATE-GRADE SCIENCE PROGRAM. - Parker, Bertha M. (Elementary School Journal, 1937)
The article analyzes the role of reading in an intermediate-grade science course at the University of Chicago in Illinois. Learning the method of science requires good reading ability to achieve the general goals of the course. Reading material renders a way by which children can integrate better in the class and broaden their experiences within the areas of science concerned. Hence, It suggests that reading materials should be in varied types which could boost children's interest in science.